Variable‐Wavelength Quick Scanning Nanofocused X‐Ray Microscopy for In Situ Strain and Tilt Mapping. Issue 6 (21st January 2020) - Richard, Marie‐Ingrid; Cornelius, Thomas W.; Lauraux, Florian; Molin, Jean‐Baptiste; Kirchlechner, Christoph; Leake, Steven J.; Carnis, Jérôme; Schülli, Tobias U.; Thilly, Ludovic; Thomas, Olivier
Abstract: Compression of micropillars is followed in situ by a quick nanofocused X‐ray scanning microscopy technique combined with 3D reciprocal space mapping. Compared to other attempts using X‐ray nanobeams, it avoids any motion or vibration that would lead to a destruction of the sample. The technique consists of scanning both the energy of the incident nanofocused X‐ray beam and the in‐plane translations of the focusing optics along the X‐ray beam. Here, the approach by imaging the strain and lattice orientation of Si micropillars and their pedestals during in situ compression is demonstrated. Varying the energy of the incident beam instead of rocking the sample and mapping the focusing optics instead of moving the sample supplies a vibration‐free measurement of the reciprocal space maps without removal of the mechanical load. The maps of strain and lattice orientation are in good agreement with the ones recorded by ordinary rocking‐curve scans. Variable‐wavelength quick scanning X‐ray microscopy opens the route for in situ strain and tilt mapping toward more diverse and complex materials environments, especially where sample manipulation is difficult. Abstract : Variable‐wavelength quick scanning X‐ray microscopy is demonstrated to be a new in situ tool that provides access both to the rotation of the crystalline lattice and to the strain field inside micro‐ and nanostructures under mechanical load. It offers new opportunities to study the mechanical behavior at small scales in situ as well as in heavy and complex environments.